2012
DOI: 10.2527/jas.2010-3340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary organic and inorganic selenium on antioxidant status, embryo development, and reproductive performance in hyperovulatory first-parity gilts1

Abstract: This project aimed to determine the effect of Se as inorganic Na-selenite (MSe) or organic Se-yeast (OSe) on antioxidant status, hormonal profile, reproductive performance, and embryo development in first-parity gilts. Forty-nine gilts were allocated to 1 of the 3 dietary treatments starting at first pubertal estrus and lasting up to 30 d after AI: control [CONT: basal diet (Se = 0.2 mg/kg) without added Se; n = 16], MSe (CONT + 0.3 mg/kg of MSe; n = 16), and OSe (CONT + 0.3 mg/kg of OSe; n = 17). Blood was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
8
35
0
Order By: Relevance
“…This was observed in spite of a lack of effect on embryo SeGPX activity (Fortier et al 2012). The metabolic and physiological mechanisms involved in such responses deserve further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…This was observed in spite of a lack of effect on embryo SeGPX activity (Fortier et al 2012). The metabolic and physiological mechanisms involved in such responses deserve further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…Then, it is mineralised to selenide and Se phosphate (9)(10)(11) and resynthesised into a seleno-cysteinyl moiety that modulates gene expression and activates Sedependent enzyme, GSH-Px (9,12) . This metabolic control was observed recently in pigs (13) by studying homoeostasis of Se-dependent GSH-Px during the peri-estral period under oxidative pressure (Fig. 1).…”
Section: Effects Of Amino Acids On Reproductive Performance Of the Sowsmentioning
confidence: 93%
“…In a recent experiment, the importance of pyridoxine for an adequate flow of organic Se (Se-cysteine) towards the GSHPx system was demonstrated in response to oxidative pressure induced by the peri-estrus period in sows (14) . Indeed, gene expressions of GSH-Px and Se-cysteine oxidase (control of the flow of Se-cysteine to the GSH-Px system) in the Peri-oestral period (d) for days -4, -3, -2, -1, 0, 1, 2 and 3 (adapted from (13) ).…”
Section: Effects Of Amino Acids On Reproductive Performance Of the Sowsmentioning
confidence: 99%
“…Fortier et al (2012), reported that the GPx in yellow bodies (CL) from ovaries of treated with Se pigs was greater that in the control group. Concerning the other main characteristics of CL including weight, diameter, total number or Se content, authors didn't find the treatment effect (22).…”
Section: Discussionmentioning
confidence: 99%